Properties and Applications of Alginates - Deniz, Irem; Imamoglu, Esra; Keskin-Gundogdu, Tugba (IntechOpen, 2022)
Alginates are biodegradable, biocompatible, renewable, and natural polysaccharides in brown marine algae. Properties and Applications of Alginates provides an overview of the state of the art of chemical and material properties of alginates and biomedical and nanotechnology mechanisms underlying alginate biosynthesis. It discusses alginate-based materials' fundamentals that combine research and technological advances with current limitations. Moreover, novel technologies using alginate composites are introduced, and as well as the latest developments in alginate-based technologies were reviewed. It also examines potential uses of alginates in immobilized biocatalysts, nanoparticle synthesis, wastewater treatment, heavy metal removal, agriculture, pharmaceuticals, and biomedicine.